Against Moral Fictionalism - Husi, Stan (2014)
Moral nihilists need an answer: if moral discourse is fatally flawed, how are we to proceed? A popular option is fictionalism, to uphold the flawed discourse in the mode of a fiction. My thesis is that fictionalism is not the best available answer to the nihilist; a better one is revisionism, the proposal to refashion the discourse so as to cure it of all flaws. Should it be possible to revise the discredited practice, by removing what is erroneous while keeping what is beneficial, the twisted allegiance to the original practice already recognized as flawed which characterizes fictionalism becomes entirely moot. Fictionalism fully worked out, I argue in this paper, is going to lead us to the very doorsteps of revisionism.
Keywords: moral revisionism; moral fictionalism; error-theory; moral nihilism